Forecasting Thailand’s exports to ASEAN with non-linear models - Petchaluck Boonyakunakorn (2018)
© Springer International Publishing AG 2018. This work focuses on forecasting Thailand’s exports to ASEAN. Thailand’s exports to ASEAN reveal an overall increasing trend with a fluctuation since Thailand’s exports are integrated in the global economy. However, the linear model might not be able to capture the behavior of Thailand’s exports to ASEAN. Linear model cannot be applied in some phenomena such as fluctuation and structural breaks in time series data. In this study, we find that the Thailand’s exports-to-ASEAN time series is non-linear via test of linearity, and find that there are two thresholds. Therefore, we forecast Thailand’s exports to ASEAN with non-linear models. We employ four non-linear models, SETAR, LSTAR, MSAR, and Kink AR model. The simple linear AR model is also applied to compare with the non-linear models. To evaluate the forecasting performance of five different models, we use RMSE and MAE as criteria. The forecasting results indicate that the SETAR model is better than the other models. However, it is still not clear cut to conclude that the non-linear models outperform linear model. However, we can conclude that the SETAR is the most suitable for forecasting Thailand’s exports to ASEAN compared with other non-linear models.